A metacognitive decision making based-framework for bank customer loyalty measurement and management - Ferreira, Fernando A. F.; Jalali, Marjan S.; Meidutė-Kavaliauskienė, Ieva; Viana, Bianca A. C. P. (Technological and Economic Development of Economy, 2015)
Bank customer loyalty is becoming a priority concern for banking institutions, as a means of gradually increasing complementary margins and eliminating the lack of liquidity caused by the current economic climate. Following a top down process, this focus culminates at the branch level, where banks’ front office employees are seen as a driving-force for building customer loyalty. At the same time, however, the difficulty in identifying and operationalizing the factors or determinants that most contribute to creating and maintaining bank customer loyalty has long been recognized. In this sense, based on the integrated use of cognitive maps and measuring attractiveness by a categorical based evaluation technique (MACBETH), this study proposes a multiple criteria framework for bank customer loyalty measurement and management. The results show that our framework allows bank customers with higher rates of customer loyalty to be identified and, from a benchmarking perspective, indicates what best practices should be followed to boost long-term relationships. Implications for scholars and practitioners are discussed.